Estudio de la sulfoxidacion organo-litotrófica y litotrófica bajo condiciones desnitrificantes - Beristain Cardoso, Ricardo (Universidad Autónoma Metropolitana, 2007)
The discharges of wastewaters coming from the petrochemical industry have great relevance world wide, due to the presence of aromatic compounds, ammonium and high concentrations of sulfide mainly, which have an adverse impact in natural ecosystems and public health. Thus, it is necessary to find and to characterize biological systems that remove compounds from residual waters discharges avoiding further deterioration to the water bodies. In this work the organo-lithotrophic and lithotrophic denitrification were studied either batch or continuous culture. For the study of organo-lithotrophic denitrification, the denitrifying sludge used for inoculating batch and continuous cultures was obtained from a UASB reactor, which had efficiencies of sulfide, phenol and nitrate consumption of 100%. In batch cultures it was observed a complete oxidation of sulfide and phenol which was coupled to the nitrate reduction when this was supplemented at stoichiometric concentrations. The sulfide and phenol oxidation was sequential, first sulfide was oxidized to sulfate, and phenol was successively consumed. The reactions rates found were: qS 2- > qS 0 = qSO4 2- > q phenol. When initial sulfide concentration was increased from 20 to 26 and 32 mg/L the specific rates of sulfide oxidation were not significantly affected, while denitrifying metabolism for phenol oxidation was affected accumulating N2O. It was also observed a diminishing on specific rates of phenol and nitrate consumption. In order to study the phenol and sulfide consumption in continuous mode, the simultaneous phenol and sulfide oxidation at different loading rates was evaluated employing a denitrifying inverse fluidized bed reactor. The phenol, sulfide and nitrate loading rates achieved were 167 mg phenol-C/L-d, 37 mg S2-/L-d and 168 mg NO3 - - N/L-d at HRT of 0.9 d. Consumption efficiencies in the steady state of phenol, sulfide and nitrate were 100%, reaching an inorganic carbon yield of 0.82 g/g phenol-C consumed, sulfate yield of 0.99 ± 0.04 g SO4 2--S/g sulfide consumed and molecular nitrogen yield of 0.89 ± 0.06 g N2/g NO3 - -N consumed. When microbial analyze of 16S rDNA on denitrifying biofilm was made, it was observed some microorganisms such as Thiobacillus denitrificans, Thiobacillus sp. and T. sajanensis, which possibly participated in the sulfide and phenol consumption. These are the first results where is shown the simultaneous phenol and sulfide oxidation using a denitrifying biofilm reactor. There are few evidences in a continuous stirrer tank reactor fed with sulfide, nitrate and acetate where S0 , N2 and CO2 were the end products. In the present work being phenol instead of acetate, sulfide was mainly oxidized to SO4 2- and the S0 concentration was very low. Thus, batch cultures mode was employed to investigate the kinetics of lithotrophic denitrification linked to S0 , thiosulfate and sulfide. The results showed that denitrification rates were affected by the type of sulfur compound. It was seen that the order of the reaction rates found were: S2O3 2- > S2- > S0 . Also was investigated the effect of S0 , sulfide and nitrate initial concentration on the kinetics of lithotrophic denitrification. The rate of denitrification increased with S0 concentration. Nonetheless, the initial sulfide concentration had an inhibitory effect on the denitrification rates. When different nitrate initial concentrations were tested, it was observed that the S2-/NO3 - molar ratio influenced in the type of final product during the sulfide oxidation. A substoichiometric concentration of nitrate could be used to promote partial oxidation to S0 , as no sulfate was produced. Although the S0 has low solubility, in the previous experiments was evidenced that increasing the S0 concentration, the denitrification rates increased. Considering this, it was evaluated as a possible technological alternative a packed bed reactor with an ratio 1:1 of sufur:limestone granules for removing nitrate. The packed bed reactor after 30 d and with 15 h as hydraulic retention time reached a removal rate of 161 mg NO3 - -N /L-d. The consumption efficiency of nitrate was 100%, being the end product molecular nitrogen. The nitrate concentrations tested in this work were concentrations typically found in the groundwater (18 mg NO3 - -N /L). Using the information of this work, together with that found in the literature, in chapter of recommendation is presented a possible proposal for the wastewater treatment from the petrochemical industry.; Las descargas de aguas residuales provenientes de la Industria Petroquímica tienen gran relevancia a nivel mundial, por la presencia de compuestos aromáticos, amonio y altas concentraciones de sulfuro principalmente; los cuales tienen un impacto adverso en los ecosistemas naturales y en la salud pública. Debido a esto, cobra importancia la necesidad de desarrollar y caracterizar sistemas biológicos que permitan que las descargas de aguas residuales no causen un deterioro a los cuerpos receptores de agua. En este trabajo se estudió la desnitrificación organo-litotrófica y litotrófica, tanto en cultivos en lote como en continuo. Para el estudio de la desnitrificación organo-litotrófica, el lodo desnitrificante utilizado para los cultivos en lote y en continuo fue obtenido de un reactor UASB, el cual tuvo eficiencias de consumo de sulfuro, fenol y nitrato de 100%. En cultivos en lote se observó una oxidación completa de sulfuro y fenol acoplado a la reducción de nitrato a N2, cuando el nitrato se alimentó a concentraciones estequiométricas. La oxidación de sulfuro y fenol fue secuencial, primero el sulfuro se oxidó a sulfato, y consecutivamente el fenol se consumió. Las velocidades de reacción encontradas fueron: qS 2- > qS 0 = qSO4 2- > q fenol. Cuando la concentración inicial de sulfuro se incrementó de 20 a 26 y 32 mg/L la velocidad de oxidación del sulfuro no se afectó significativamente, mientras que el metabolismo desnitrificante para la oxidación de fenol se vio afectado, con una acumulación de N2O y una disminución en la velocidad de consumo de fenol y nitrato. Con la finalidad de estudiar el consumo de fenol y sulfuro en continuo, la oxidación simultánea de fenol y sulfuro se evaluó a diferentes velocidades de carga utilizando un reactor de lecho fluidificado inverso desnitrificante. Las velocidades de carga alcanzadas fueron de 167 mg C-fenol/L-d, 37 mg S2-/L-d y 168 mg NNO3 - /L-d a un TRH de 0.9 d. En el estado estacionario desnitrificante las eficiencias de consumo de fenol, sulfuro y nitrato fueron de 100%, alcanzando rendimientos de producto de 0.82 ± 0.04 C-inorgánico/g C-fenol consumido, 0.99 ± 0.04 g S-SO4 2-/g S2- consumido y 0.89 ± 0.06 g N2/g N-NO3 - consumido. El análisis molecular del 16S rDNA en la biopelícula desnitrificante mostró algunas bacterias tales como Thiobacillus denitrificans, Thiobacillus sp., y T. sajanensis, las cuales tal vez pudieron haber participado en el consumo de fenol y/o sulfuro. Estos son los primeros resultados donde se evidencia la oxidación simultánea de fenol y sulfuro empleando un reactor de biopelícula desnitrificante. Hay escasas evidencias en un reactor continuo de tanque agitado alimentado con acetato, sulfuro y nitrato, donde los productos finales fueron CO2, S0 y N2. En el presente trabajo siendo utilizado el fenol en vez de acetato, el sulfuro se oxidó principalmente a sulfato. Por lo tanto, se emplearon cultivos en lote para investigar la cinética de la desnitrificación litotrófica acoplada a la oxidación de S0 , S2O3 2- y S2-. Los resultados mostraron que la velocidad de desnitrificación se afectó por el tipo de compuesto azufrado. El orden de las velocidades de reacción fueron: S2O3 2- > S2- > S0 . También se investigó el efecto de la concentración inicial de S0 , sulfuro y nitrato sobre la cinética de la desnitrificación litotrófica. La velocidad de desnitrificación incrementó con la concentración inicial de S0 . No obstante, la concentración inicial de sulfuro tuvo un efecto inhibitorio en la velocidad de desnitrificación. Cuando se probaron diferentes concentraciones iniciales de nitrato, se observó que la relación molar S2-/NO3 - influyó en el producto final formado durante la oxidación del sulfuro. A una concentración sub-estequiométrica de nitrato se promovió la formación de S0 en vez de sulfato. A pesar de que el S0 tiene baja solubilidad, en los experimentos previos se evidenció que al incrementar la concentración inicial de S0 se incrementó la velocidad de desnitrificación. Considerando esto, se evaluó como una posible tecnología alternativa un reactor de lecho empacado con S0 -limestone para eliminar el nitrato. El reactor de lecho empacado después de 30d de operación y a un TRH de 15h, alcanzó una velocidad de carga de 161 mg N-NO3 - /L-d. La eficiencia de consumo de nitrato fue de 100%, siendo el nitrógeno molecular el producto final. Las concentraciones de nitrato probadas en este trabajo son concentraciones que típicamente podemos encontrar en las aguas subterráneas (18 mg N- NO3 - /L). Utilizando la información de este trabajo, junto con lo reportado en la literatura, en la sección de recomendaciones se presenta una posible propuesta para tratar el agua residual de la Industria Petroquímica.